Peran Orientasi Budaya dalam Berkarier Wirausaha pada Siswa SMK - Wibowo, Doddy Hendro; Sarajar, Dewita Karema (UIN Sunan Kalijaga, 2023)
Entrepreneurship is a potential job that still has the opportunity to be developed. The purpose of this study was to determine whether there is an influence of cultural orientation and gender on entrepreneurial careers. Researchers use purposive sampling method, involving 347 Vocational High School (SMK) students consisting of 180 male students (51.87%) and 167 female students (48.12%). The researcher used the High School Student Entrepreneurial Orientation Scale and the Cultural Orientation Scale. The results of this study indicate the influence of cultural orientation on entrepreneurship in vocational students. The results also showed that there was no difference in entrepreneurial interest between male and female students. The practical implication of the results of this study is that the vertical and horizontal collective cultural orientation factors have a role in building entrepreneurial interest among teenagers.